Mortalidade perinatal: aspectos, sentimentos e perspectivas sob o olhar da gestão e dos enfermeiros - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Perinatal mortality is one of the serious problems that afflict public and private health in Brazil. Its impacts are differentiated in each region, but the perinatal mortality rate is worrisome, which drives the need to verify its causes and forms of minimization. This study aimed to identify the positions of nurses and hospital managers regarding perinatal death. In order to achieve this goal, it was necessary to understand the role of the Mãe Paranaense Program in the reduction of perinatal death, to identify the theoretical position regarding the theme and to verify if theory and practice are allied in the analysis of the data collected. From a bibliographical review, qualitative, basic and with interview use, content analysis was established from the work of Bardin (1977). Registry Units were selected and, from this, context units were enumerated and verified. It was possible to perceive that the majority of managers and nurses are aware of the weaknesses of the health system, the lack of multidisciplinary and interdisciplinary work, the scarcity of investment resources for physical, human and technological structure, among other items. It was also emphasized that there is still a lack of capacity to work with the Paranaense Mother Protocol, as well as relative ignorance of many of its bases. Nurses and managers also see improvements for the scenario, but point out that it is necessary to modify the general structures so that the ideal plan is palpable.
Keywords: Enfermagem; Gestão; Análise de conteúdo; Mortalidade Perinatal; Nursing; Content Analysis; Management; Perinatal mortality; CNPQ::CIENCIAS DA SAUDE